IMPLEMENTASI PROGRAM PEMBUATAN AKTA KEMATIAN DI KECAMATAN TUGU KOTA SEMARANG - Laras, Dena; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The implementation of death certificate program in Tugu sub-district, part of Semarang city is government’s effort in managing population documents and administration. The government’s role, especially coming from Department of Population and Civil Registration of Semarang city, is important in the implementation process. The department is in the position of where they are obliged to overcome challenges in population administration practice based on Act 24 Year 2003 about Amendment of Act 23 Year 2006 about Population Administration. This study is based on qualitative descriptive method, using staffs from Department of Population and Civil Registration of Semarang and Tugu sub-district residents that have been involved in the program as informants. This study aims to analyze the policy implementation process and its impeding factors. This study uses George Edward III, which stated that the impeding factors in a policy implementation process are communication, resources, and disposition or bureaucratic structure and behaviour issues. Based on the result found from this study, it is shown that the implementation of this program is still lacking on resources, such as human resources, financial resources, and facility resources. This program also still lacks on socialization efforts by the policy makers. Hence, it can be concluded that this program’s implementation process has not been optimal and ill-implemented.